Open Government and Linked Data: Concepts, Experiences and Lessons Based on the Mexican Case - Quintanilla, Gabriela; Gil-García, José Ramón (Revista del CLAD Reforma y Democracia, 2016)
Currently, governments and individuals are surrounded by information and a great number of databases are everywhere and include data about very diverse matters. It is possible to find data about production, services, commerce, environment, public policies, or legislation, among others. Data could be shared, grow every day, and could be potentially used to improve the quality of life, develop new businesses or help solving diverse social problems. When data can be accessed and used freely, they are considered open data that can be linked to configure big data networks. Because governments are among the largest producers of data and information, linking open governmental data becomes a great opportunity to promote the principles of open government. This paper presents some basic concepts about open data and linked data and relates them to the available Mexican public sector data, as an example. Results lead to think about the need to achieve a greater use of open government data for generating public value.
Keywords: Open Government; Open Data; E-Government; Information Technology